Preliminary Note - Henrieke Stahl (Internationale Zeitschrift für Kulturkomparatistik)
This volume brings together contributions addressing the intersections of political poetry, performativity, and the internet. The essays are based on presentations given at workshops and conferences organized by the DFG Centre for Advanced Studies “Russian-Language Poetry in Transition: Poetic Forms of Dealing with Boundaries of Genre, Language, Culture and Society between Europe, Asia and America” (2017-2023). The conferences took place in 2018-2019, at a time when neither the coronavirus pandemic nor Russia’s brutal invasion of Ukraine were foreseeable, and the contributions have not been updated in light of these catastrophes. The articles presented here deal with recent poetry and focus on the connection between politics, performativity, and the internet in multiple literatures and intercultural relations. Although the majority of these texts belong to the Russophone world, poetry from Serbia, Latvia, and China is also considered. The contributors demonstrate, on the one hand, how newer poetry softens genre distinctions and formally tends towards multimedia hybridization and, on the other, how it transcends or dissolves linguistic, cultural, and social boundaries. Dr. Ekaterina Friedrichs and Ms. Lena Rosalin Schwarz were involved in preparing this publication for printing. We would like to thank them both for their careful review and wonderful cooperation.